2017
DOI: 10.1016/j.ajoc.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Unusually very late-onset new growth of intraocular retinoblastoma: A case report and review of literature

Abstract: PurposeTo report a patient who presented with a very late-onset new growth of intraocular retinoblastoma, which occurred 11 years after the initial combined treatment.ObservationsA 12-year-old monoophthalmic female patient presented with bilateral familial retinoblastoma showing new growth of intraocular tumor after 11 years of complete regression following combined local and systemic treatments. The new tumor growth was treated with diode laser transpupillary thermotherapy, ruthenium-106 plaque radiotherapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(31 reference statements)
1
3
0
2
Order By: Relevance
“…This finding is consistent with a study conducted in the USA (34%, 95% CI: 25.7–43.4) with a median follow‐up of 5 years 24 . Another study found that a new growth of intraocular RB can occur more than 10 years after the eye responds to conservative treatment 30 . Therefore, a long‐term follow‐up of RB eyes, especially bilateral RB that receives conservation therapy, is essential.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with a study conducted in the USA (34%, 95% CI: 25.7–43.4) with a median follow‐up of 5 years 24 . Another study found that a new growth of intraocular RB can occur more than 10 years after the eye responds to conservative treatment 30 . Therefore, a long‐term follow‐up of RB eyes, especially bilateral RB that receives conservation therapy, is essential.…”
Section: Discussionsupporting
confidence: 89%
“…Although there are reports of tumor recurrences after several years following treatment completion, 13 nearly all retinal tumor recurrences will be presented by 3 years of follow-up. 3 Several studies have suggested younger age, especially below 2 years, at diagnosis is predictive of new tumor development.…”
Section: Recurrence: Retinalmentioning
confidence: 99%
“…It was difficult to differentiate regressed retinoblastoma from active recurrent retinoblastoma, due to posterior synechia and white mass precluded ophthalmoscopic visualization, even though inflammation and pain can be a warning sign of the recurrence RB. Overall, most commonly tumor regrowth appeared in the eyes of children diagnosed at a very young age or those with family history of RB 3 which is absent in the current case. We performed enucleation followed by histopathology examination to determine the diagnosis, which clarified the tissue as undifferentiated retinoblastoma, without rosettes and confirmed there was no sign of cornea, ciliary body and optic nerve attachment with the tumor (Fig 4,5).…”
Section: Case Descriptionmentioning
confidence: 46%